Avaliação da permeabilidade da zona de gotejamento de um alto-forno com foco na análise dos fenômenos de retenção e refluxo - Dimas Henrique Barros Andrade (2017)
The operation of the blast furnaces has been increasingly hampered due to the chemical and physical qualities of the available raw materials, either because of their impoverishment over the years or because of the high cost of those that still have quality. The quality of the raw materials, mainly coke and sinter, are paramount in all zones of the reactor, but in this work the focus will be on the dripping zone. The quality of the charged coke that arrives in the dripping zone, the liquid flow and the gas flow are critical factors to define the permeability of this region, all of which have to coexist in that location with the least possible turbulence. In the dripping zone there are 3 natural streams for the 3 protagonists mentioned above: the coke is consumed from the surface to the center and descends, the liquids, hot metal and slag, drip and the gas rises. Wherein liquids and gas have to pass in a countercurrent flow through the voids between the coke particles. Several studies have already been carried out on fluid dynamics in packaged beds, and in this thesis the similarity of these conditions of the dripping zone of a blast furnace was discussed, in order to understand the dynamics of liquids and solid in this region related to operational factors and raw materials quality. The main understanding was the relationship between total liquid volumes (hot metal production and slag-rate) and slag and coke quality with operational instability, so it was possible to identify the limits or necessary adjustments when one or more of the variables change from the typical condition. The focus of this knowledge on the volume of liquids and gases means higher productivity for the blast furnaces of Gerdau Ouro Branco, which generates value for the company with the reduction of fixed costs or the opportunity to increase production if there is market demand. The work was conducted based on the analysis of the historical data of Gerdau Ouro Branco. These data served as a basis for estimating the critical variables and these were used to plot each moment of the blast furnace operational conditions in flooding diagram. The plotting in the diagram indicated limits for operation when there were operational instabilities and it was possible to quantify the impact of each critical variable, so it is possible to propose actions of operational adjustment aiming at a higher liquid production